Assessment of the properties of sprayed coatings for the thermal barrier applied to the piston of internal-combustion engine - Keiji SONOYA (The Japan Society of Mechanical Engineers, 2014)
The properties of three thermal sprayed coatings (Coating①: Top coat; Al2O3, Bond coat; Ni-Cr, Coating②: Top coat; YSZ, Bond coat; CoNiCrAlY, Coating③: SUS316) were compared to select the effective sprayed coating for giving the thermal barrier to the Al alloy components of internal-combustion engine. The results are as follows. (1) After thermal cycle test, there was not any crack and delamination in the coating③, and a partial cracks and delamination were observed at the top coating in coating① and ②. (2) The coating①, ② and ③ have sufficient adhesion strength. The adhesion strength of coating② was specially high. (3) The thermal barrier property of the coating② was better than that of coating① and coating③. (4) In the result of comprehensive evaluation, the coating② had good thermal barrier property and the coating③ was a reasonable material because of low cost as the thermal sprayed coating applied to the Al alloy components of internal-combustion engine.